Spin‐Crossover Properties of an Iron(II) Coordination Nanohoop. Issue 7 (14th December 2020) - Heras Ojea, María José; Van Raden, Jeff M.; Louie, Shayan; Collins, Richard; Pividori, Daniel; Cirera, Jordi; Meyer, Karsten; Jasti, Ramesh; Layfield, Richard A.
Abstract: Addition of the bipyridyl‐embedded cycloparaphenylene nanohoop bipy[9]CPP to [FeH2 B(pyz)2 ] (pyz=pyrazolyl) produces the distorted octahedral complex [Fe(bipy[9]CPP)H2 B(pyz)2 2 ] (1 ). The molecular structure of 1 shows that the nanohoop ligand contains a non‐planar bipy unit. Magnetic susceptibility measurements indicate spin‐crossover (SCO) behaviour with a T 1/2 of 130 K, lower than that of 160 K observed with the related compound [Fe(bipy)H2 B(pyz)2 2 ] (2 ), which contains a conventional bipy ligand. A computational study of 1 and 2 reveals that the curvature of the nanohoop leads to the different SCO properties, suggesting that the SCO behaviour of iron(II) can be tuned by varying the size and diameter of the nanohoop. Abstract : Addition of a bipyridyl embedded cycloparaphenylene (CPP) nanohoop to [FeH2 B(pyz)2 ] (pyz=pyrazolyl) produces the distorted octahedral complex [Fe(bipy[9]CPP)H2 B(pyz)2 2 ]. Its spin‐crossover (SCO) properties are strongly influenced by a distortion associated with the nanohoop, implying that variations in nanohoop size may provide a way of tuning the SCO properties of iron compounds.